Konsep dan Karakteristik Wali Allah dalam Surat Yunus Ayat 62 - Muhammad Fery (Tafhim Al-'Ilmi, 2023)
This study aims to examine and analyze Waliyullah in the holy book of the Qur’an, Surat Yunus verse 62. This research started with the erroneous understanding of the community towards the concept of Waliyullah, the community assumed what they got, but all the allegations that he received as the basis were very distorted by explanation of the Qur’an so that researchers are interested in analyzing the concept and characteristics of Waliyullah in Surat Yunus verse 62 and how to get guardianship in the perspective of the Qur’an. The path and the outline rules in this study have the aim of finding a truth about the concepts and characteristics of Waliyullah which are contained in Surat Yunus verse 62. This study is of the type of literature (library research) and this study uses a descriptive and thematic analysis method to analyze. Then the inductive method is used by the researcher in drawing a conclusion that has been generated from the analysis. The results of this study are: first, Waliyullah, are people who do not have anxiety or sadness within themselves. Secondly, Waliyullah who always has faith and belief in the One and Only God and his Prophet, he always does what Allah commands and stays away from what is forbidden, gets good news in this world and the hereafter. Third, those who leave warok worldly affairs, towards something that has no benefit to them, are kind and not angry towards believers, then are harsh towards the Quraysh infidels. Keywords: concept, Waliyullah, Surat Yunus Verse 62